2017
DOI: 10.1007/s12298-017-0452-9
|View full text |Cite
|
Sign up to set email alerts
|

The expression of a candidate cucumber fruit sugar starvation marker gene CsSEF1 is enhanced in malformed fruit induced by salinity

Abstract: The cucumber ( L.) gene () was suggested to be a good marker gene for sugar starvation in fruit. The expression of this gene in fruits is dramatically upregulated in plants that have suffered either complete defoliation or prolonged darkness. was initially discovered as a gene that was upregulated during somatic embryogenesis. We examined the difference in fruit parts and the effect of pollination on the upregulation of induced by defoliation treatment. The results indicated that the upregulation of in fruit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(32 reference statements)
0
4
1
Order By: Relevance
“…The variation of the data was much larger than that reported previously (Tazuke and Asayama 2013; Tazuke et al 2015; Tazuke et al 2017). The study of the effect of salinity on fruit growth revealed that the RGR of a fruit in which growth was suppressed by salinity tended to fall to about 1.5% h -1 (Tazuke 1997).…”
Section: Gene Expression Analysiscontrasting
confidence: 59%
See 1 more Smart Citation
“…The variation of the data was much larger than that reported previously (Tazuke and Asayama 2013; Tazuke et al 2015; Tazuke et al 2017). The study of the effect of salinity on fruit growth revealed that the RGR of a fruit in which growth was suppressed by salinity tended to fall to about 1.5% h -1 (Tazuke 1997).…”
Section: Gene Expression Analysiscontrasting
confidence: 59%
“…In our previous studies, the expression of the AS, CsSEF1, and CsFDI1 genes in young fruit increased similarly in response to total defoliation, prolonged darkness, salinity, and fruit harvest (Tazuke et al 2015;Tazuke et al 2017;Tazuke and Kinoshita 2018). This correlation could explain the di culty in delineating the causes of gene expression, such as sugar starvation and growth cessation.…”
Section: Discussionmentioning
confidence: 88%
“…In these three genes, the upregulation of the genes was mainly seen on 6 DAA. Because the expression of these three genes was tested in many experiments (Tazuke and Asayama, 2013;Tazuke et al, 2015;Tazuke et al, 2017;Tazuke and Kinoshita, 2018;Tazuke et al, 2019), it is highly likely that they are good markers of sugar starvation, although the gene function is known only in AS. Thus, in fruits whose RGR became close to zero, it is most probable that severe sugar starvation is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of candidate sugar starvation genes together with the reduction of hexose concentration close to zero strongly suggests that the candidate genes are genuine sugar starvation markers. In an experiment removing the ovary, it was suggested that stopping of sugar import (loss of sink activity) together with the remaining growth activity causes sugar starvation (Tazuke et al, 2017). Thus, loss of sink activity may occur in slow growing fruits, and it is possible to hypothesize that sugar starvation caused by loss of sink activity triggers fruit abortion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation